Effects of mipomersen, an apolipoprotein B100 antisense, on lipoprotein (a) metabolism in healthy subjects - Nandakumar, Renu; Matveyenko, Anastasiya; Thomas, Tiffany; Pavlyha, Marianna; Ngai, Colleen; Holleran, Stephen; Ramakrishnan, Rajasekhar; Ginsberg, Henry N.; Karmally, Wahida; Marcovina, Santica M.; Reyes-Soffer, Gissette (Journal of lipid research, 2018)
Elevated lipoprotein (a) [Lp(a)] levels increase the risk for CVD. Novel treatments that decrease LDL cholesterol (LDL-C) have also shown promise for reducing Lp(a) levels. Mipomersen, an antisense oligonucleotide that inhibits apoB synthesis, is approved for the treatment of homozygous familial hypercholesterolemia. It decreases plasma levels of LDL-C by 25% to 39% and lowers levels of Lp(a) by 21% to 39%. We examined the mechanisms for Lp(a) lowering during mipomersen treatment. We enrolled 14 healthy volunteers who received weekly placebo injections for 3 weeks followed by weekly injections of mipomersen for 7 weeks. Stable isotope kinetic studies were performed using deuterated leucine at the end of the placebo and mipomersen treatment periods. The fractional catabolic rate (FCR) of Lp(a) was determined from the enrichment of a leucine-containing peptide specific to apo(a) by LC/MS. The production rate (PR) of Lp(a) was calculated from the product of Lp(a) FCR and Lp(a) concentration (converted to pool size). In a diverse population, mipomersen reduced plasma Lp(a) levels by 21%. In the overall study group, mipomersen treatment resulted in a 27% increase in the FCR of Lp(a) with no significant change in PR. However, there was heterogeneity in the response to mipomersen therapy, and changes in both FCRs and PRs affected the degree of change in Lp(a) concentrations. Mipomersen treatment decreases Lp(a) plasma levels mainly by increasing the FCR of Lp(a), although changes in Lp(a) PR were significant predictors of reductions in Lp(a) levels in some subjects.